How to measure anything in cybersecurity risk - Hubbard, Douglas W. 1962-; Seiersen, Richard 1967- (Wiley, 2023)
"Cybersecurity has become one of the biggest risks facing companies today. There is a need to provide the tools and information for a CISO to become more of a chief information risk officer so they are better able to identify and prioritize risk, allocate resources, and develop effective risk mitigation strategies. This book helps to fill that need"--